Wsparcie osób z niepełnosprawnościami podczas pandemii wirusa COVID-19 - Strzelecki, Dominik (Zeszyty Naukowe Pedagogiki Specjalnej, 2022)
The beginning of 2020 turned the lives of all people around the world upside down. Regardless of the level of intelligence, predisposition or material status, people have faced a new and very difficult situation related to the outbreak of the COVID-19 pandemic. Due to cognitive deficits, people with disabilities have difficulties in understanding the current situation and the resulting changes, such as: remote education, masks and social distance. This article reviews the rapidly changing legal situation of people with disabilities and their families since the outbreak of the pandemic in Poland. The author presents solutions taken by the legislator in Poland to support people with disabilities. In addition, the author proposed possible forms and strategies for supporting people with disabilities in education, which will allow students to provide a substitute for pre-pandemic education and to use the time of distance learning in the most effective way.